Microspore Induced Doubled Haploids Production from Ethyl Methanesulfonate (EMS) Soaked Flower Buds Is an Efficient Strategy for Mutagenesis in Chinese Cabbage - Lu, Yin; Dai, Shuangyan; Gu, Aixia; Liu, Mengyang; Wang, Yanhua; Luo, Shuangxia; Zhao, Yujing; Wang, Shan; Xuan, Shuxin; Chen, Xueping; Li, Xiaofeng; Bonnema, Guusje; et al. (Frontiers in Plant Science, 2016)
Chinese cabbage buds were soaked with Ethyl methanesulfonate (EMS) to induce mutagenesis. The influence of different EMS concentrations and treatment durations on microspore development, embryo production rate and seedling rate were evaluated in five Chinese cabbage genotypes. Mutations in four color-related genes were identified using high resolution melting (HRM) curves of their PCR products. The greatest embryo production and seedling rates were observed when buds were treated with 0.03 to 0.1% EMS for 5 to 10 min, while EMS concentrations greater than 0.1% were lethal to the microspores. In total, 142 mutants with distinct variations in leaf shape, leaf color, corolla size, flower color, bolting time and downy mildew resistance were identified from 475 microspore culture derived Doubled Haploids. Our results demonstrate that microspore derived Doubled Haploids from EMS soaked buds represents an efficient approach to rapidly generate homozygous Chinese cabbage mutants.